PENGARUH CORPORATE SOCIAL RESPOSIBILITY TERHADAP RASIO PROFITABILITAS (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2022)
The purpose of this study was to determine and analyze the effect of Corporate Social Responsibility on Return on Assets (ROA), Return on Equity (ROE), Net Profit Margin (NPM), and Earnings per Share (EPS) in Mining Companies Listed on the Indonesia Stock Exchange. during the 2018-2020 period. This type of research is quantitative research. The sampling technique used is a purposive technique. The population in this study were 49 companies and after being selected through the criteria determined by the researcher, the sample size was found to be 3 companies. The data analysis technique in this study used descriptive analysis, classical assumption test, simple linear regression analysis, partial test, and coefficient of determination. The data analysis technique was assisted by using SPSS version 25. The results of this study show that (1) Corporate Social Responsibility (CSR) disclosure does not have a significant effect on Return on Assets(ROA), (2) Corporate Social Responsibility (CSR) disclosure does not has a significant effect on Return On Equity (ROE), (3) Corporate Social Responsibility (CSR) disclosure has no significant effect on Net Profit Margin(NPM), (4) Corporate Social Responsibility (CSR) disclosure has no significant effect to Earnings Per Share(EPS).